Environmental science - Miller, G. Tyler (Brooks/Cole, 2013)
Emphasizes natural capital, natural capital degradation, solutions, trade-offs, and importance of individuals. This title helps you to learn how nature works, how you interact with it, and how people have sustained - and can continue to sustain - our relationship with the earth by applying nature's lessons to economies and individual lifestyles.